Keragaman Fusarium pada Rizosfer Tanaman Kacang Panjang dan Peranannya bagi Pertumbuhan Tanaman - Rahmi Sutrisni; Widodo . (Jurnal Fitopatologi Indonesia, 2012)
Fusarium wilt caused by Fusarium oxysporum f.sp. tracheiphilum is one of the important diseases on yard long bean. Besides of its capability of causing diseases in plants, some species of Fusarium are non pathogenic and able to control Fusarium wilt as naturally occured in disease suppressive soils. The objective of this study was to observe the rhizosphere Fusarium diversity and its role on the plant growth of yard long bean. Out of 56 isolates collected during the study, four species were identified, including F. oxysporum (39.3%), F. semitectum (28.6%), F. longipes (12.5%), F. solani (5.3%), and one unidentified Fusarium sp. (14.3%). The highest diversity index was obtained from the field planted with corn as previous crop. In general, 56 isolates tested could be differentiated into 3 groups based on their effects on plan growth, i.e.: deleterious that caused wilting or growth suppressive without wilting (50.0%), neutral that no significantly difference growth as untreated (41.1%), and growth promoting (8.9%). All three isolated Fusarium causing plant wilting identified as F. oxysporum, while isolates with growth promoting effect were identified as F. oxysporum (4 isolates) and F. solani (1 isolate). These five selected growth promoting Fusarium also suppressed the wilt disease and increased the plant growth when co inoculated with wilt pathogen of yard long bean, F. oxysporum f.sp. tracheiphillum.Key words: diversity, Fusarium, long yard bean, rhizosphere